Viable Pearls and Seashells: Marine Culture and Sustainable Luxury in Broome, Western Australia - Condello, Annette (Springer Nature, 2021)
This chapter traces the origin of pearls and seashells as underwater luxury goods from a global-historical and marine-cultural perspective within the sustainability debate. It illuminates the luxury of the hidden sea gems, its natural and imitation items, refers to writings concerning jewellery ethnography and discusses the impact of the connections between the pearl, fashion and tourism industries in Western Australia. Contributing to creating Broome’s viable marine-culture, it analyses the popularity of the Australian pearl and pearl shell overseas as well as relooking at the jewellery traders who introduced the luxury of the indigenous “ritual good” to an international market in the context of “sustainable luxury”. The chapter concentrates on the display of the Western Australian indigenous commodity in newspapers and magazines from the 1930s to the 1960s. Suggesting how the indigenous integration of seashell luxury emerged in Australia’s Northwest, the town of Broome impacted the multicultural pearling industry not only through jewellery, but also by providing an alternative solution for pearl fishery farms. The viability of the pearl industry demonstrates how the natural jewel has contributed to the meaning of sustainable luxury, transforming how to measure coastal remnants in the Kimberley region. Broome’s marine culture developed a form of Australian pearlescence as a sustainable luxury, with Paspaley and Kailis jewellery injected with authenticity, reliability and organic substance.